Interaction of Lipids, Mean Platelet Volume, and the Severity of Coronary Artery Disease Among Chinese Adults: A Mediation Analysis - Yao, Yao; Li, Xiaoye; Wang, Zi; Ji, Qiuyi; Xu, Qing; Yan, Yan; Lv, Qianzhou (Frontiers in Cardiovascular Medicine, 2022)
Objective: Currently, coronary artery disease (CAD) is regarded as one of the leading global disease burdens. Evidence proved that platelet activation in dyslipidemia induced CAD, however, their interaction has not been well-established in vivo. This study aims to assess the mediation effects of mean platelet volume (MPV) in lipids and the severity of CAD. Methods: We prospectively enrolled 5188 consecutive subjects who underwent coronary angiography between 2015 and 2020. Participants were grouped according to their CAD events, which was defined as stenosis ≥ 50% in at least one coronary artery and whose severity was evaluated by Gensini score (GS). A lipid index was drawn by principal component analysis to weight related lipid parameters including total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), non-HDL-C, apolipoprotein (apo) A1 and apoB. The interaction of lipids and MPV in atherosclerosis was evaluated by mediation analysis. Results: Lipid index increased with elevated GS irrespective of statin status (not on statin: β=0.100, P<0.001; on statin: β=0.082, P<0.001). Multiple linear regression indicated positive correlation between MPV and GS after adjustment (β=0.171, P<0.001). Subjects in the highest MPV tertile had higher levels of atherogenic lipid parameters and lipid index (P<0.001). The adjusted odds ratios were greater among individuals undergoing statin medications who had high GS and higher MPV levels by elevated lipid index tertiles [1.168 (0.893-1.528) vs 2.068 (1.552-2.756) vs 1.764 (1.219-2.551)]. The combination of lipid index and MPV provided better prediction for high GS than individual lipid index or MPV as shown by receiver-operating characteristic (ROC) curves (areas under ROC curves were 0.700 and 0.673 in subjects on or not on statin treatment). Significantly, mediation analysis revealed the mediation interaction of lipid index on GS by MPV, whose effect size reached 20.71% and 20.07% in participants with or without statin medications. Conclusion: The increased risk of dyslipidemia on CAD was partly enhanced by elevated MPV levels, whose mediating effect was around 20%.